Deepsea fungi of the eastern tropical Pacific of Costa Rica: morphological, genetic, and enzymatic characterization - Rodríguez Ramírez, Ivonne; Solano-González, Stefany; Cortés, Jorge; Rojas-Jiménez, Keilor (Frontiers in Marine Science, 2025)
IntroductionFungal communities have only been studied in a small portion of the vast variety of habitats that exist in deepsea environments, and studies aimed at understanding fungal diversity and function are minimal.ObjectiveThe aim of this study is to explore both the fungal diversity in deepsea sediments and the enzymatic activities present in them, which are related to the ecological roles of the strains and their biotechnological potential.MethodsEighteen sediment samples from three expeditions to deepsea areas of the Eastern Tropical Pacific (ETP) of Costa Rica were analyzed. Fungi were cultured on R2A medium, followed by physical characterization and molecular analysis (ITS and whole-genome sequencing) for the taxonomic identification of the strains. Once pure cultures were established, enzymatic tests for cellobiase, chitinase, lipase, cellulase, peroxidase, and laccase activities were performed, as well as surfactant activity.ResultsFifty-five fungal strains were isolated, and genetic analysis was conducted on 27 strains, of which 7.41% belong to the Basidiomycota group and 92.59% to Ascomycota. These strains are distributed across 14 species. Among the identified strains are Periconia LEGMi281a and Hortaea LEGMi415c. Two strains exhibited cellobiase and chitinase activity, one strain exhibited cellulase activity, and one exhibited laccase production. None of the species exhibited lipase or peroxidase activity, and no clear surfactant activity was detected. Whole-genome sequencing revealed significant size differences compared to reference genomes.ConclusionThe enzymatic activities of the strains suggest they may play a role in the degradation of organic matter and nutrient recycling, similar to terrestrial fungal counterparts. The differences in genome sizes, with the genomes of Periconia LEGMi281a and Hortaea LEGMi415c being larger than the reference genomes, pave the way for future research into deepsea adaptations, reflected in genetic changes. Additionally, the strains were identified as having high biotechnological potential.